Discrepancy between mRNA and protein expression of tumour suppressor maspin in synovial tissue may contribute to synovial hyperplasia in rheumatoid arthritis. Issue 10 (10th September 2004) - Schedel, J; Distler, O; Woenckhaus, M; Gay, R E; Simmen, B; Michel, B A; Müller-Ladner, U; Gay, S
Abstract : Objective: To investigate the expression of maspin in RA synovial tissue and compare it with the expression in osteoarthritis (OA) and normal synovial tissue (NS). Methods: Using specific primers for maspin, a 237 bp fragment was amplified from cDNA obtained from cultured RA, OA, and normal synovial fibroblasts (SF) by RT-PCR. Additionally, mRNA expression levels were determined quantitatively by real time PCR. mRNA expression of maspin was investigated on snap frozen and paraffin embedded synovial tissue sections by in situ hybridisation. Immunohistochemistry was used to identify the cell type expressing maspin. SDS-PAGE and western blotting were performed to evaluate the protein expression in cultured SF. To confirm protein synthesis in situ, immunohistochemistry with specific anti-maspin antibodies was performed in synovial tissue sections of patients with RA. Results: RT-PCR showed expression of maspin in all cDNA samples from cultured SF. Maspin mRNA was found to be decreased in RA SF twofold and 70-fold compared with OA SF and NS SF, respectively. Maspin mRNA was expressed in RA, OA, and normal synovial tissue. Importantly, maspin transcripts were also found at sites of invasion into cartilage and bone. At the protein level, maspin could be detected in RA and, less prominently, OA SF. In RA synovial tissue, maspin protein was detected in only a few synovial lining cells. Conclusion: Maspin is expressed intensively in RA SF at the mRNA level, but only slightly at the protein level, possibly owing to down regulation of maspin; this may contribute to the hyperplasia of synovial tissue in RA.